2021
DOI: 10.3390/ani11113269
|View full text |Cite
|
Sign up to set email alerts
|

Activity Pattern and Correlation between Bat and Insect Abundance at Wind Turbines in South Sweden

Abstract: We present data on species composition and activity of bats during two years at three different wind- turbines, located in south Sweden, both at the base and nacelle height. To test the hypothesis that bats are attracted to wind turbines because of feeding opportunities, insects were sampled at nacelle height at one wind turbine using a suction trap, simultaneously as bat activity were measured. At this wind turbine, we also compared two different technical systems for ultrasound recordings and collect meteoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Rydell et al (2017) reported that 90% of bat activity recorded at turbines (~ 100 m high, averaged over 10 min, several wind parks between 2012–2015) occurred when winds were less than 5.8 m s ‐1 and temperatures were greater than 14.6°C. de Jong et al (2021) also measured average nightly bat activity in response to weather conditions recorded at the turbine nacelle at 3 turbines for two seasons and found that 90% of bat activity occurred when temperatures were greater than 9°C and wind speeds were less than 8.2 m s ‐1 . Even if temperature is a stronger driver of bat activity than wind speeds, wind speed in relation to turbine rotation speeds should be considered when trying to predict bat activity near active turbines as well as potential collision risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rydell et al (2017) reported that 90% of bat activity recorded at turbines (~ 100 m high, averaged over 10 min, several wind parks between 2012–2015) occurred when winds were less than 5.8 m s ‐1 and temperatures were greater than 14.6°C. de Jong et al (2021) also measured average nightly bat activity in response to weather conditions recorded at the turbine nacelle at 3 turbines for two seasons and found that 90% of bat activity occurred when temperatures were greater than 9°C and wind speeds were less than 8.2 m s ‐1 . Even if temperature is a stronger driver of bat activity than wind speeds, wind speed in relation to turbine rotation speeds should be considered when trying to predict bat activity near active turbines as well as potential collision risks.…”
Section: Discussionmentioning
confidence: 99%
“…The recording environment on turbines and similar structures tends to be poorer than typical ground-level deployments and can be expensive to deploy and maintain suggesting it may not always be an effective monitoring tool (Voigt et al 2021). Studies which have paired ground-level and at height bat acoustic monitoring frequently find that the patterns observed between the two types of detectors are similar, even if the volume of data collected is contrasting, but make it possible to detect some high-flying species more effectively (Collins and Jones 2009) and predict fatalities at wind turbines (Roemer et al 2019, Barré et al 2023). de Jong et al (2021 found that the bat activity at nacelle height was more varied than from groundlevel detectors, within and between years.…”
Section: Monitoring At Heightmentioning
confidence: 99%
“…The presence of insects in the vicinity of turbines is assumed to be at least partially responsible for bird and bat activity around turbines [6], [24]. Nevertheless, we are unaware of studies that have documented insects and their possible influence on birds and bats around offshore turbines.…”
Section: Discussionmentioning
confidence: 99%
“…Parallels can be drawn between land development for solar PV and for wind turbines, especially in terms of habitat modification. Bats have been studied extensively in relation to wind energy, encompassing fatalities at turbines potentially caused by collision, flight paths affected by vortices, turbines being mistaken for roosts, used as mating sites and because insect prey can be attracted to turbines (Baerwald et al, 2008; Cryan, 2008; Cryan & Barclay, 2009; Cryan et al, 2014; Dahl et al, 2012; de Jong et al, 2021; Horn et al, 2008; Rydell et al, 2016; Voigt et al, 2022). Wind turbines also cause habitat loss due to bats avoiding surrounding wind turbines farms (Barré et al, 2018, 2022; Minderman et al, 2012, 2017).…”
Section: Introductionmentioning
confidence: 99%